Programa de auditoría financiera para el componente cuentas y documentos por pagar Ecuador Banana S.A. - Ramirez Neira, Adriana Lizbeth (My University, 2021)
In the current environment it has been noted that there are companies that have gone bankrupt due to the fact that within their operations, acts such as embezzlement, fraud within their finances have been committed, which prevents them from continuing with their activities and deciding to close their operations Having said this, the objective of this work is to prepare the audit program for the accounts and documents payable component under the evaluation of the inherent risk and control risk. for which a descriptive research is carried out, compiling information from scientific articles, in order to obtain the necessary information for the preparation of the theoretical framework and subsequently design the financial audit program. It is concluded that the importance of internal control is due to the fact that it allows knowing the correct procedure of the operations carried out within a company or organization that allows efficient management of its resources.
En el ámbito actual se ha podido notar que existen empresas que han quebrado debido a que dentro de sus operaciones se han cometido hechos como la malversación de fondos, fraudes dentro de sus finanzas, lo que les impide seguir con sus actividades y deciden cerrar sus operaciones, dicho esto, el objetivo de este trabajo es elaborar el programa de auditoria para el componente cuentas y documentos por pagar bajo la evaluación del riesgo inherente y riesgo de control. para lo cual se realiza una investigación de tipo descriptiva recopilando información de artículos científicos, para lograr obtener información necesaria para la elaboración del marco teórico y posteriormente diseñar el programa de auditoria financiera. Se concluye que la importancia de un control interno se debe a que permite conocer el correcto proceder de las operaciones que se realizan dentro de una empresa u organización lo que les permite gestionar eficientemente sus recursos.
Keywords: AUDITORIA FINANCIERA; CUENTAS POR PAGAR; CONTROL INTERNO